Alligatorweed Stem Borer (suggested common name) Arcola malloi Pastrana (Insecta: Lepidoptera: Pyralidae: Phycitinae): EENY764/IN1300, 8/2020 - Wells, Bonnie Cook; Minteer, Carey (EDIS, 2021)
Includes: Introduction - Synonymy - Distribution - Description - Life Cycle - Hosts - Importance - Selected References This publication is also available on the Featured Creatures website at http://entnemdept.ufl.edu/Creatures/BENEFICIAL/alligatorweed_stem_borer.htm